Social interaction in second language chat rooms - Jenks, Christopher Joseph (Studies in social interaction., 2014)
Examines social interaction in second language voice-based chat rooms. How do speakers of English as an additional language manage their talk and interaction in chat rooms? Christopher Jenks thoroughly analyses the interactional effects of technology, and explores in detail the social and linguistic implications of communicating in second language chat rooms. Providing a unique look at how second language talk is organized in an online setting, this book is essential reading for postgraduate students and scholars in computer-mediated communications, social interactions, TESOL and applied linguistics. It focuses on voice-based chat rooms instead of text-based ones, adding to and enriching the existing body of research on second language textbooks within computer-mediated communication studies. It contains multiple transcripts and figures to illustrate the discussion